Trade liberalization and regional integration: implications for 2020 - Robinson, Sherman; DeRosa, Dean A. (International Food Policy Research Institute, 1995)
After seven years of arduous negotiations under the auspices of the General Agreement on Tariffs and Trade (GATT), the Uruguay Round of multilateral trade negotiations was concluded in late 1993. The United States approved the agreement in late 1994, in time for the 1995 commencement of the new World Trade Organization (WTO), which will implement the agreement and provide the major forum for future trade negotiations. There have been a number of quantitative studies of the impact of world trade liberalization and of the formation of subregional free trade areas such as the North American Free Trade Agreement (NAFTA), Mercosur in South America, and the new Asia Pacific Economic Cooperation (APEC). Most of these studies focus on the impact of changes in policy, analyzing the efficiency gains and structural changes that might be induced by changes in import protection. The goal of such studies is not to project the future but to analyze the empirical mechanisms by which policy changes affect the world economy. In this brief, the authors discuss studies of world trade liberalization and studies of regional trading areas. Finally, they state that recent quantitative studies generally find that global trade liberalization yields substantially larger economic benefits, including benefits to agriculture, than the proliferation of regional trading arrangements. Thus, while increasing regionalism is emerging as an important element of the current international political economy, it is not a desirable outcome in itself.